Study on Crack Growth Resulting from Spacing and Alignment of Two Circular Holes: A Phase Field Approach - Alfat, Sayahdin (Computer Assisted Methods in Engineering and Science; Vol 31 No 4 (2024)DO - 10.24423/cames.2024.1620, 2024)
This study investigates the effects of spacing and alignment between two circular holes on crack growth simulation. Key aspects analyzed include: (a) crack growth behavior, (b) von Mises stress distribution, and (c) energy profiles, all through variations in the spacing and alignment of the holes. The material is assumed to be homogeneous and isotropic, with the following non-dimensional properties: Young’s modulus E = 70, Poisson's ratio  ν = 0.35, which correspond to the real values E = 70 GPa, ν = 0.35, and ɣ = 2800 J · m –2 . Additionally, the body force is neglected ( f ( x ; t ) = 0). The numerical method used in this research is the adaptive finite element method, which is considered highly robust for solving the phase field model for crack growth. Notable findings include: (a) spacing between the two holes did not significantly alter the crack path, while alignment differences had a significant impact; (b) during the cracking process, the highest stress occurs at the crack tip and the lowest at the crack center; and (c) the time for cracking in materials with two holes varies with spacing and alignment, and elastic and surface energy curves help predict total damage.